EXPLORING THE EPIDEMIC OF DRUG ADDICTION IN KASHMIR: UNDERSTANDING ITS ROOT CAUSES - Sarfaraz Ahmad Rather; Irfan Ahmad Mir (PT. Radja Intercontinental Publishing, 2023)
Abstract Drug addiction, a complex and deeply entrenched issue, has emerged as a global challenge transcending borders and affecting diverse communities. This paper delves into the multifaceted nature of drug addiction, exploring its physiological, psychological, and social dimensions. From the initial allure to the devastating consequences, it examines the factors that drive individuals towards substance abuse and the subsequent impact on their health, relationships, and society at large. Through this exploration, the paper sheds light on the importance of comprehensive prevention, intervention, and rehabilitation strategies, as well as the need for empathy and understanding in addressing this pressing concern. Ultimately, it advocates for a collective effort to break the cycle of addiction and provide pathways to recovery and healing.